WACANA BERITA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) PADA KUMPARAN.COM PERIODE JULI 2021 (ANALISIS SEMIOTIKA SOSIAL M.A.K HALLIDAY) - Benni Handayani; Oktalisa, Nurul Eka (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
Reporting on the Implementation of Restrictions on Community Activities (PPKM) has become a national issue that is reported by the media which raises pros and cons in the community. This study aims to determine how the analysis of social semiotics on PPKM news on the news site coil.com. Michael Alexander Kirkwood (M.A.K) Halliday's Social Semiotics is included in the Discourse Analysis model which is able to find out how the content of texts, messages are packaged and delivered with three concepts including the field of discourse, discourse involvement, and means of discourse. In this study, the researcher used a qualitative descriptive research method with observation, documentation, and interview data. This study emphasizes seeing the analysis of social semiotics applied by the coil.com site related to PPKM news for the period 21-25 July 2021. The results show that in this study there is an alignment of the media towards the government as seen from the delivery of government programs very well, presenting sources with disproportionate appearance only appear as the main sources from the government in a monologue, and coil.com tries to minimize public disappointment with the choice of the right language style to make readers understand more about the content of the news.